Analysis of risk factors for surgical site infection in spinal surgery patients and study of direct economic losses - Qiuxia Zuo; Kexin Zhao; Baoji Dong; Yuan Zhou; Xiao Wang; Adila Maimaiti; Ping Tian (BMC Musculoskeletal Disorders)
Abstract Background Surgical site infection (SSI) is a serious complication of spine surgery, leading to prolonged hospital stays, re-operations, and economic losses. The aim of the study was to explore the types and quantities of pathogenic bacteria involved, the incidence of SSI, and to identify the independent risk factors and direct economic impact on patients with postoperative SSI in spine surgery. Methods The medical records of spine surgery patients from January 2023 to April 2024 at two hospitals in Xinjiang were retrospectively reviewed. Patients with SSIs were included in the case group, and patients without SSIs were matched 1:1 based on hospital, department, age ± 5 years, primary diagnosis, and the specific surgery type. They were then subjected to univariate and multivariate paired logistic regression analyses. The Wilcoxon signed-rank test was used to compare differences in hospitalization costs and duration of stay between the two groups. Results A total of 38 individuals, or 0.63% of the 6018 adults who had spinal procedures, experienced SSI. Findings from the univariate analysis demonstrated a statistically significant correlation between SSI (p < 0.05), intraoperative bleeding of 300 ml or more, and the duration of indwelling drain use. Many separate risk variables for SSI were found by multivariate regression analysis: combined underlying diseases (OR 2.634, 95% CI 1.02–6.78), days with an indwelling urinary catheter (OR 1.38, 95% CI 1.01–1.88), and days with an indwelling drain (OR 1.449, 95% CI 1.01–2.07). The most prevalent bacteria identified as causing skin infections were Staphylococcus aureus and Staphylococcus epidermidis. About $1,688.50 in direct economic loss was attributable to SSI in patients undergoing spine surgery. Conclusions The presence of combined underlying diseases, extended use of indwelling urinary catheters, and prolonged use of indwelling drains significantly increase the risk of SSI in spine surgery patients.